Analysis Politeness And Impoliteness Youtube Chanel"Prabowo Subianto Bicara Gagasan Mata Najwa: English - Evi Lestaria; Desi Purnama Sari; Budiman (EDUJ : English Education Journal, 2024)
Politeness and impoliteness are integral aspects of pragmatics, deeply embedded in the fabric of social interaction. This study aims to analyze the manifestations of politeness and impoliteness in the live verbal interactions featured on the YouTube channel "Mata Najwa." Specifically, the focus is on the episode titled "Prabowo Subianto Bicara Gagasan Mata Najwa." By examining the discourse in this episode, the study seeks to elucidate how conversational strategies either adhere to or deviate from societal norms of politeness. Such an analysis is pivotal for understanding the dynamics of communication and the implicit power relations within social interactions. The findings can provide valuable insights into the mechanisms of face-saving and face-threatening acts, contributing to the broader field of pragmatics and its application to real-life media interactions. This investigation underscores the relevance of politeness theory in contemporary digital communication platforms.